The Usefulness of Reporting in Crisis Management for Decision Making - Ryszard ORLIŃSKI (Communications of International Proceedings, 2021)
Crisis management is about preventing crisis situations, preparing to take control over them as part of planned activities, removing their effects and restoring resources. An important element in management is the use of information about the events that have occurred. The article focuses on the possibilities of using the data reported within the information system and the usefulness of this data for decision making. The background for the article was the pandemic threat that engulfed the world in connection with the appearance of the SARS-CoV-2.
Keywords: Pandemic; Crisis Management; Reporting; Information System